Нанесені на активне вугілля Pd- і Pd, Au-каталізатори в реакціях окиснення водню та монооксиду вуглецю - Gerasimyuk, I. P.; Zazhigalov, V. A.; Lapko, V. F.; Lysenko, A. O.; Tarasenko, Yu. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2004)
Catalytically active phases based on active carbon supported Pd and Pd-Au have been synthesized by the method of reductive sorption. Their physicochemical properties and catalytic activity have been studied in reactions of H2 and CO oxidation.